Peran Baby Massage Sebagai Stimulasi Nonfarmakologis Untuk Meningkatkan Berat Badan Bayi Usia 6 Bulan - Siti Fithrotul Umami (Jurnal Ners, 2025)
Weight is a crucial indicator in assessing infant development. Six-month-old infants are in the transition stage from exclusive breastfeeding to complementary feeding, thus requiring extra encouragement to support optimal growth. A non-pharmacological intervention that has been proven effective is infant massage. This research aims to explain the role of baby massage as a non-pharmacological stimulation in increasing the weight of six-month-old infants at the Ny. "Prigen M." Subdistrict Primary Health Center (TPMB). The research design used a pre-test post-test control group design. A sample of 30 six-month-old infants was selected using a purposive sampling technique, consisting of 15 treatment groups and 15 control groups. The intervention carried out was infant massage for 15–20 minutes with a frequency of three times a week for four weeks. Weight was measured using a digital scale. Data analysis used a Paired Sample t-test. The findings of this research indicate a significant difference between weight before and after the intervention in the treatment group, while the control group showed no significant changes. This research proves that baby massage is effective in increasing weight in 6-month-old babies and can be recommended as a simple, safe, and practical intervention in obstetric services and home infant care.